Pengelolaan Sarana dan Prasarana Pendukung Ramah Lingkungan di Sekolah Adiwiyata (Studi di SMAN 4 Tangerang Selatan) - Rahmat Fauzi; Sujiyo Miranto; Silvan Erusani (Neolectura, 2022)
This study aimed to determine the management of environmentally friendly facilities and infrastructure at Adiwiyata School, Study at SMAN 4 South Tangerang. This research is a combination research of sequential explanatory model with survey method to collect data from samples that represent the main data with questionnaires, structured interviews and so on. The sample used in the study amounted to 128 students, 25 educators, 7 janitors, and 6 canteen traders. The percentage of student questionnaire data shows 73% of students and the percentage of teacher questionnaire data shows 83% of educators in the management of supporting facilities and infrastructure in schools. Some things that need to be done optimally by the school, namely the avaibility of separate bins, music rooms accompanied by noise suppressors, biogas and organizational structure to manage school sanitation facilities. In addition, improving the quality of healthy and environmentally friendly canteen services needs to be improved